STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN (KUALIFIKASI AKADEMIK DAN KOMPETENSI) DI SMPIT AT- TAUBAH KARAWANG - Syukur Nurhasan Fauzi; Zahra Nuriyah, Tazkia Kautsar Azhar; Tia Amelda Febriani, Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to describe the implementation of academic qualification standards and educator competencies at SMPIT At-Taubah Karawang. The focus of the study lies in how teachers and educational staff meet professional standards through academic qualifications, a series of scientific competency development programs, and ongoing programs. The research method used is descriptive qualitative with data collection techniques through interviews and observations. The results show that teachers at SMPIT At-Taubah have academic qualifications that are in line with national standards while integrating Islamic boarding school traditions, such as the obligation to read the Qur'an well, memorize at least Juz 30, and teach yellow books. In addition, the school routinely conducts teacher competency evaluations, provides opportunities to participate in training from various institutions, and encourages professional development through seminars and workshops. These findings show that collaboration between schools, foundations, and external institutions plays an important role in maintaining the quality of learning. Thus, strengthening academic qualifications and teacher competencies has proven to be a major factor in improving the quality of Islamic-based education that is adaptive to current developments.